PEMBELAJARAN MATEMATIKA REALISTIK DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI OPERASI BILANGAN PECAHAN PADA SISWA KELAS VII SMP PGRI 3 PAGA TAHUN PELAJARAN 2016/2017 - Yohana Sina (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2018)
This research was conducted in SMP PGRI 3 Paga with the reason of the low learning outcomes in the process of learning mathematics. Mathematics learning is transmitif means teaching applying concepts directly to students and the use of less-varied learning methods that is still using conventional learning with lecture methods that cause students quickly bored with mathematics learning. This can lead to low student learning outcomes. In order for mathematics learning to be active, creative and fun learning, it can be done through the application of realistic mathematics learning model that emphasizes on student activity and interaction among students to motivate and help each other in mastering the material. The design of this study is a classroom action research conducted in two cycles. Each cycle consists of planning, execution, observation, and reflection. The subjects of this study were students of Class VIIA SMP PGRI 3 Paga. Data collection techniques used observation methods, interviews, questionnaires, test results, and discussions with subject teachers, using qualitative data analysis. The result of research shows that (1) the application of realistic mathematics learning cycle I increases to 65,55% (enough category) (2) in cycle II increase to 75,28% (good category). The conclusion of this research is realistic mathematics learning model can improve student learning result class VII SMP PGRI 3 Paga on the matter of fractional operation.